Theoretico-experimental analysis of bistability in the oscillatory response of a TaOx ReRAM to pulse train stimuli - Schmitt, N.; Ascoli, A.; Messaris, I.; Demirkol, A. S.; Menzel, S.; Rana, V.; Tetzlaff, R.; Chua, L. O. (Frontiers in Nanotechnology, 2024)
Fading memory is the capability of a physical system to approach a unique asymptotic behaviour, irrespective of the initial conditions, when stimulated by an input from a certain class. Standard stimuli from the AC periodic class typically induce fading memory effects in nonvolatile memristors, as uncovered for the first time back in 2016. Very recently, a deep investigation of resistance switching phenomena in a TaO x Resistive Random Access Memory cell revealed the capability of the nano-device to exhibit one of two possible oscillatory behaviours, depending upon the initial condition, when subject to a particular periodic excitation. This interesting finding was however left unexplained. Bistability is the simplest form of local fading memory. In a system, endowed with local fading memory under a given stimulus, the initial condition does not affect the long-term behaviour of the state as long as it is drawn from the basin of attraction of either of the distinct coexisting state-space attractors (two limit cycles for the periodically-forced memristor acting as a bistable oscillator). Here the history of the system, encoded in the initial condition, is thus erasable only locally through ad hoc stimulation. Motivated by the discovery of local history erase effects in our Resistive Random Access Memory cell, this study applies a powerful system-theoretic tool, enabling the analysis of the response of first-order systems to square pulse train-based periodic stimuli, and known as Time Average State Dynamic Route, to an accurate physics-based mathematical model, earlier fitted to the nano-device, to determine a strategy for specifying the parameters of an excitation signal, consisting of the sequence of two square pulses of opposite polarity per period, so as to induce various forms of monostability or multistability in the non-volatile memristor. In particular, as an absolute novelty in the literature, experimental measurements validate the theoretical prediction on the capability of the device to operate as one of two distinct oscillators, depending upon the initial condition, under a specific pulse train excitation signal.